Reversible Paralysis and Loss of Deep Pain Sensation After Topical Intrathecal Morphine Administration Following Durotomy. Issue 1 (12th April 2014) - Chamisha, Yael; Shamir, Merav H.; Merbl, Yael; Chai, Orit
<x xml:space="preserve">Abstract</x> Objective To report 2 dogs that developed temporary pelvic limb paralysis with loss of deep pain sensation after topical intrathecal morphine administration during spinal surgery. Study Design Clinical report. Animals Dogs (n = 2). Methods A 5‐year‐old castrated male French Bulldog with a subarachnoid diverticulum at T9–T10 and a 9.5‐year‐old castrated male Belgian Shepherd dog with a herniated disc at T12–T13 and intradural component, had Gelfoam soaked with morphine placed over the dura mater defect. Results Pelvic limb paralysis and loss of deep pain sensation was noticed immediately after recovery from anesthesia. After intravenous naloxone administration, both dogs immediately regained ambulation and normal pain sensation; however the effect was temporary lasting only a few hours. Permanent resolution of clinical signs occurred 24 hours after surgery. Conclusions Topical intrathecal morphine administration resulted in temporary pelvic limb paralysis and loss of deep pain sensation. This route of administration should be used cautiously until further determination of the efficacy and adverse effects associated with topical intrathecal morphine administration.